The anthropology of buddhism & hinduism : Weberian themes - Gellner, David. N. (New Delhi : Oxford Unoversity Press., 2003)
With reference to Nepal.
Includes references and index.
Keywords: Buddhism -- Social aspects -- Nepal; Hinduism -- Social aspects -- Nepal